Profit Sharing dalam Pengelolaan Rumah Makan â€œPadangâ€ - Solihin, Fauzi (Journal the Winners: Economics, Business, Management, and Information System Journal, 2004)
Article discusses profit sharing in running a â€œPadangâ€ restaurant. Profit sharing always increase sense of belonging every employee andÂ  supportÂ  theÂ Â  managementÂ Â  function.Â  ItÂ Â  canÂ Â  beconcluded that profit sharing can motivated employee to increase working performance and increase sense of belonging and responsibility. It also can increase continuous improvement team work between employee.